Engineering p‐Orbital States via Molecular Modules in All‐Organic Electrocatalysts toward Direct Water Oxidation - Li‐Hong Yu; Xue‐Feng Zhang; Zi‐Ming Ye; Hong‐Gang Du; Li‐Dong Wang; Ping‐Ping Xu; Yuhai Dou; Li‐Ming Cao; Chun‐Ting He (Advanced Science)
Abstract Oxygen evolution reaction (OER) is an indispensable anode reaction for sustainable hydrogen production from water electrolysis, yet overreliance on metal‐based catalysts featured with vibrant d‐electrons. It still has notable gap between metal‐free and metal‐based electrocatalysts, due to lacking accurate and efficient p‐band regulation methods on non‐metal atoms. Herein, a molecular modularization strategy is proposed for fine‐tuning the p‐orbital states of series metal‐free covalent organic frameworks (COFs) for realizing OER performance beyond benchmark precious metal catalysts. Optimized combination of benzodioxazole/benzodiimide‐based building blocks achieves an impressive applied potential of 1.670 ± 0.004 V versus reversible hydrogen electrode (RHE) and 1.735 ± 0.006 V versus RHE to deliver enhanced current densities of 0.5 and 1.0 A cm−2, respectively. Moreover, it holds a notable charge transfer amount (stands for a long service life) within operation period that outperforms all reported metal‐free electrocatalysts. Operando differential electrochemical mass spectrometry (DEMS) with isotope labeling identifies the adsorbate evolution mechanism (AEM). A variety of spectroscopic techniques and density functional theory (DFT) calculations reveal that the p‐band center of these catalysts can be shifted stepwise to optimize the oxygen intermediate adsorption and lower the reaction energy barrier. This work provides a novel perspective for enhancing the electrocatalytic performance of metal‐free COFs.